(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the medical system of Abu Ali ibn Sina (Avicenna, 980-1037), indications for the use of more than 1,500 simple and about 800 complex medicines are presented as part of the "opposite to opposite" therapy tactics. Failure to comply with the requirements of this therapy tactic can cause a sharp deterioration in the condition of patients suffering from type 2 diabetes mellitus, gout, certain forms of cancer, urolithiasis and cholelithiasis, as well as a number of other pathological conditions, the pathogenesis of which is associated with the development of metabolic syndrome.